Interception of Class III malocclusion with facemask: cases' report - Hajar Benhaioun; Soukaina Sahim; Amal El Aouame; Farid El Quars (Elsevier, 2021)
Introduction: A skeletal Class III malocclusion is one of the most difficult anomalies to treat. Class III malocclusion with retruded maxilla can be orthopedically corrected with facemask in deciduous or mixed dentition in mild to moderate cases. The treatment should be carried out as early as possible before the malocclusion becomes severe. Cases' report: These are two case reports of successful treatment of developing skeletal class III malocclusion, on a 7-year-old female patient in early mixed dentition and on a 9-year-old female patient in mixed dentition. Both present a skeletal Class III due to a deficient maxilla. The treatment plan included protraction of the maxilla by a reverse pull Delaire type facemask. The post treatment results showed significant improvement in Class III skeletal relationship and the facial profile, with the correction of the overjet. Discussion: The purpose of early orthodontic treatment of Class III is to intercept the developing malocclusion and redirect it to physiological development. Cases that show skeletal maxillary retrognathism are cases opt for treatment with facemask. The latter acts by promoting maxillary growth while restricting mandibular growth. Thus, it improves the skeletal relationships, minimizes excessive dental compensation and improves occlusal function. It also provides more pleasing facial aesthetics and may eliminate the necessity for orthognathic surgery treatment in some cases. Conclusion: Early Class III treatment can be done successfully when proper diagnosis and proper treatment plan are carried out carefully.